Exploring Student Learning Strategies for Overcoming Speaking Anxiety - Tribunga, Dinda Sepia; Ithriyah, Siti (Universitas Pahlawan Tuanku Tambusai, 2025)
This study used a qualitative descriptive approach to investigate students speaking anxiety strategies at SMA Negeri 34 Jakarta in the context of English language learning to overcome their fear of speaking. The data collect through semi-structure in depth interviews. A total of 12 grade XI students participated in this study, consisting of 5 boys and 7 girls, with ages ranging from 16-17 years old. The data collected were to analyzed using thematic analysis method, which included coding, classification, and identification of themes and sub themes. The result show that most students experience moderate levels of anxiety. The results show that most students experience moderate levels and supportive English learning methods can help students overcome affective barriers such as speaking anxiety